2001
DOI: 10.1016/s1074-7613(01)00231-x
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of CD43 from the Immunological Synapse Is Mediated by Phosphorylation-Regulated Relocation of the Cytoskeletal Adaptor Moesin

Abstract: Formation of the immunological synapse requires TCR signal-dependent protein redistribution. However, the specific molecular mechanisms controlling protein relocation are not well defined. Moesin is a widely expressed phospho-protein that links many transmembrane molecules to the cortical actin cytoskeleton. Here, we demonstrate that TCR-induced exclusion of the large sialoprotein CD43 from the synapse is an active event mediated by its reversible binding to moesin. Our results also reveal that relocalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
238
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(254 citation statements)
references
References 52 publications
(4 reference statements)
13
238
2
1
Order By: Relevance
“…Ezrin is present in a phosphorylated form in cells before stimulation through Fas, antigen receptors or chemokine receptors, and is dephosphorylated after these stimulations (Kondo et al, 1997;Delon et al, 2001;Brown et al, 2003;Faure et al, 2004;Gupta et al, 2006;Hao et al, 2009). Our observation that ezrin was dephosphorylated after FasL stimulation in T cells (Figure 1c) is in accordance with those reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ezrin is present in a phosphorylated form in cells before stimulation through Fas, antigen receptors or chemokine receptors, and is dephosphorylated after these stimulations (Kondo et al, 1997;Delon et al, 2001;Brown et al, 2003;Faure et al, 2004;Gupta et al, 2006;Hao et al, 2009). Our observation that ezrin was dephosphorylated after FasL stimulation in T cells (Figure 1c) is in accordance with those reports.…”
Section: Discussionsupporting
confidence: 92%
“…Activated ezrin and moesin are required for the formation of the distal pole complex (Allenspach et al, 2001) and for the movement of a cytotoxic cell to target cells (Mrass et al, 2008). Alternatively, lymphocyte activation and remolding involves ezrin/moesin inactivation and dissociation from cortical actin (Delon et al, 2001;Brown et al, 2003;Faure et al, 2004;Gupta et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies identified the distal SMAC (dSMAC), an outer region that contains large molecules such as CD43 and CD45 (Delon et al 2001;Freiberg et al 2002). Real time visualization of the early events of T-cell activation has given greater temporal and spatial accuracy.…”
Section: Lat Microclusters: Sites Of Nucleation Of Signaling Complexesmentioning
confidence: 99%
“…Adhesion molecules have to then hold the two cells together. ERMs have been implicated in all these processes [49,50,51] . Interestingly, a similar array of ERMmediated cytoskeletal rearrangements occurs during infection of lymphocytes by HIV-1.…”
Section: The Immunological Synapse -An Example Of Erm Functional Divementioning
confidence: 99%